2022
DOI: 10.3390/ijms231910986
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Spermidine on C2C12 Myoblasts Proliferation, Redox Status and Polyamines Metabolism under H2O2 Exposure

Abstract: A central feature of the skeletal muscle is its ability to regenerate through the activation, by environmental signals, of satellite cells. Once activated, these cells proliferate as myoblasts, and defects in this process profoundly affect the subsequent process of regeneration. High levels of reactive oxygen species such as hydrogen peroxide (H2O2) with the consequent formation of oxidized macromolecules increase myoblasts’ cell death and strongly contribute to the loss of myoblast function. Recently, particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…It stands to reason therefore that increasing GSH levels may be an effective strategy to protect cells from oxidative damage. Similar to results seen previously ( Ceci et al ., 2022a , 2022b ), we show that reductions to GSH levels in H 2 O 2 -treated C2C12 cells can be significantly blocked by morroniside pretreatment. Analysis of cellular ROS levels using DCF-DA showed that intracellular ROS production was significantly increased by H 2 O 2 stimulation, and that these were clearly restored to more normal levels through co-treatment of H 2 O 2 with morroniside.…”
Section: Discussionsupporting
confidence: 93%
“…It stands to reason therefore that increasing GSH levels may be an effective strategy to protect cells from oxidative damage. Similar to results seen previously ( Ceci et al ., 2022a , 2022b ), we show that reductions to GSH levels in H 2 O 2 -treated C2C12 cells can be significantly blocked by morroniside pretreatment. Analysis of cellular ROS levels using DCF-DA showed that intracellular ROS production was significantly increased by H 2 O 2 stimulation, and that these were clearly restored to more normal levels through co-treatment of H 2 O 2 with morroniside.…”
Section: Discussionsupporting
confidence: 93%
“…Spermine supplementation during lactation can improve the intestinal villus height: crypt depth ratio and intestinal absorption area of piglets, thus promoting their growth ( van Wettere et al, 2016 ). Spermidine can improve the antioxidant capacity of muscle cells and reduce the ratio of oxidized glutathione (GSH/GSSH) to promote cell proliferation ( Ceci et al, 2022 ). In addition, spermidine was able to reverse the decreased activity of antioxidant enzymes in the hearts of offspring caused by hypoxia in utero ( Chai et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Polyamines are generic terms for cationic organic compounds containing multiple amino groups. The chemical characteristics of polyamines allow them to function in cellular homeostasis, including in cell proliferation and differentiation[ 2 ], nucleic acid protection[ 3 ], apoptosis[ 4 ], autophagy[ 5 ], and antioxidant activity[ 6 ]. Other common polyamines found in vertebrates include putrescine, spermidine, and spermine, which are synthesized by the decarboxylation of ornithine[ 7 ].…”
Section: Introductionmentioning
confidence: 99%